A post-transcriptional mechanism pacing expression of neural genes with precursor cell differentiation status - Dai, Weijun (2016)
Nervous system (NS) development relies on coherent upregulation of extensive sets of genes in a precise spatiotemporal manner. How such transcriptome-wide effects are orchestrated at the molecular level remains an open question. Here we show that 3′-untranslated regions (3′ UTRs) of multiple neural transcripts contain AU-rich cis-elements (AREs) recognized by tristetraprolin (TTP/Zfp36), an RNA-binding protein previously implicated in regulation of mRNA stability. We further demonstrate that the efficiency of ARE-dependent mRNA degradation declines in the neural lineage because of a decrease in the TTP protein expression mediated by the NS-enriched microRNA miR-9. Importantly, TTP downregulation in this context is essential for proper neuronal differentiation. On the other hand, inactivation of TTP in non-neuronal cells leads to dramatic upregulation of multiple NS-specific genes. We conclude that the newly identified miR-9/TTP circuitry limits unscheduled accumulation of neuronal mRNAs in non-neuronal cells and ensures coordinated upregulation of these transcripts in neurons.